Early emergence of axons and formation of accessory nerve (XI) in avian embryos (Asian Journal of Medical and Biological Research, 2016)
A research work was undertaken to evaluate the feeding effect of tree forages on performance of growing sheep. Twenty growing sheep (in 4 groups) were fed three different tree forage diets. Tree forages Melia azardirachta, Leucaena leucocephala and Artocarpus heterophyllus were supplied in three treatments except one consisted no tree forages which was considered as control. There were significant (p